TAFSIR ALQURAN DENGAN AL-SUNNAH (Studi Historis-Sosiologis Al-Quran) - Intan Zakiyyah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This article discusses the interpretation of the Koran with the Sunnah. The approaches used in this paper are historical and sociological approaches. At the time of the Prophet Muhammad the interpretation of the verses of the Koran became his authority. However, he only interpreted the verses of the Qur'an which he considered important and which were asked by his companions. The source of his interpretation is the verses of the Qur'an and Sunnah. In later times like the Companions and Tabiin, the interpretation of the Qur'an continued to develop. The interpretation of the verses of the Qur'an at the time of the Prophet and his companions was known by word of mouth, because the codification of the interpretation was carried out at the end of the Umayyad empire, although the codification was still in a special chapter of the Hadith books. After that, the development of the codification of interpretation was carried out separately from the Hadith books to a special book for interpretation. Tafsir appeared at the same time as the Qur'an existed, namely when it was revealed to the Prophet Muhammad. Prophet Muhammad in interpreting the Koran there are those who use the hadith qawliyyah, fi'liyyah and also taqririyyah. In this article, we only discuss the interpretation of the Koran with al-Sunnah, the function of hadith on the Koran, the motives of the Prophet Muhammad in interpreting the Koran and the characteristics and privileges of interpreting the Koran with al-Sunnah.